2006
DOI: 10.1016/j.bbi.2006.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Placebo effects in laser-evoked pain potentials

Abstract: Placebo treatment may affect multiple components of pain, including inhibition of nociceptive input, automatic or deliberative appraisal of pain, or cognitive judgments involved in pain reporting. If placebo analgesia is due in part to an attenuation of early nociceptive processing, then pain-evoked event-related potentials (ERPs) should be reduced with placebo. In this study, we tested for placebo effects in P2 laser-evoked potentials at midline scalp electrodes. We found that placebo treatment produced signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
85
2
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 125 publications
(99 citation statements)
references
References 53 publications
9
85
2
3
Order By: Relevance
“…6). Before scanning, warm and noxious temperatures were chosen on an individualized basis for each subject (3,26,46). Warm temperatures (44-46.5°C) were chosen at calibration level 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…6). Before scanning, warm and noxious temperatures were chosen on an individualized basis for each subject (3,26,46). Warm temperatures (44-46.5°C) were chosen at calibration level 2.…”
Section: Methodsmentioning
confidence: 99%
“…After calibration, placebo and control treatments were applied to two regions of the volar forearm of each volunteer. As in previous work, before scanning, subjects also underwent an expectancy manipulation phase in which belief in the placebo was strengthened (3,26,46). The manipulation involves surreptitiously presenting reduced temperatures during stimulation on placebo-treated skin (using different skin areas from those used in scanning).…”
Section: Methodsmentioning
confidence: 99%
“…4). Electroencephalography (EEG) studies have further confirmed that placebo analgesia is associated with reduced amplitudes of event-related potentials to experimental pain stimuli (Wager et al, 2006;Watson et al, 2007;Aslaksen et al, 2011). Evidence from spinal cord forced magnetic resonance imaging (fMRI), which only recently became technically feasible in both humans and animals, has revealed that pain-related activity in the ipsilateral dorsal horn, corresponding to painful stimulation, is substantially reduced under placebo (Eippert et al, 2009b) and rises under expectations of increased pain (nocebo) .…”
Section: A Painmentioning
confidence: 98%
“…It has been shown that this may occur through both expectation and conditioning mechanisms, although expectations and emotions seem to play a fundamental role (Benedetti et al, 2003;Price et al, 2005). Most of our knowledge about the placebo effect comes from the field of pain, in which both a neuropharmacological approach with opioid antagonists (Levine et al, 1978;Grevert et al, 1983;Levine and Gordon, 1984;Amanzio and Benedetti, 1999;Benedetti et al, 1999;Hoffman et al, 2005) and, more recently, brain imaging techniques (Petrovic et al, 2002(Petrovic et al, , 2005Wager et al, 2004Wager et al, , 2006Zubieta et al, 2005;Keltner et al, 2006;Kong et al, 2006) have been used.…”
Section: Introductionmentioning
confidence: 99%